Sistem Informasi E-Campaign Pemilihan Kepala Desa Berbasis Website - Reda Meiningtiyas; Rico Andrian; Dedy Hermawan; Didik Kurniawan (Jurnal Pepadun, 2022)
Campaign are activities carried out to gain public support for potential candidates and convince them to vote for the candidate. Lack of information about the campaigns carried out by the candidates, the dissemination of information through online media. E-campaign is defined as the use of technology by prospective candidates in attracting public trust and assisting in the democratic process. The village head election e-campaign information system was built to help the community get correct information about candidates, make it easier for candidates in the campaign process and the process of collecting village head election requirements data, and make it easier for administrators to collect village head election requirements data. The system development uses the PHP programming language and the Laravel framework. The system development methodology uses the waterfall method. The waterfall method has 5 stages, namely communication, planning, modelling, construction, and deployment. System testing is done by black box testing and User Acceptance Testing (UAT). The results of the black box testing that have been carried out on the test class are presented successfully or unsuccessfully. The results of the User Acceptance Testing (UAT) that have been carried out have obtained a percentage of 81.2% which can be concluded that the e-campaign information system from user perceptions is very good.